2016
DOI: 10.1109/tevc.2016.2530311
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Co-evolutionary Module Identification with Application to Cancer Disease Module Discovery

Abstract: Module identification or community detection in complex networks has become increasingly important in many scientific fields because it provides insight into the relationship and interaction between network function and topology. In recent years, module identification algorithms based on stochastic optimization algorithms such as Evolutionary Algorithms have been demonstrated to be superior to other algorithms on small to medium scale networks. However, the scalability and resolution limit problems of these mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 76 publications
(128 reference statements)
0
5
0
Order By: Relevance
“…Genetic algorithms are advanced heuristic methods that have been successfully applied to solve hard problems involving biological optimization of given objective functions in a wide range of parameter selection and control problems. These include knockout-or partial knockdown-based metabolic engineering [28], robust systems design [29], evaluation of response to cancer treatment [30], identification of cancer glioma tumors [31], or design of chemotherapies [32].…”
Section: Multi-objective Parallel Genetic Algorithm (Pga)mentioning
confidence: 99%
“…Genetic algorithms are advanced heuristic methods that have been successfully applied to solve hard problems involving biological optimization of given objective functions in a wide range of parameter selection and control problems. These include knockout-or partial knockdown-based metabolic engineering [28], robust systems design [29], evaluation of response to cancer treatment [30], identification of cancer glioma tumors [31], or design of chemotherapies [32].…”
Section: Multi-objective Parallel Genetic Algorithm (Pga)mentioning
confidence: 99%
“…However, the robustness of algorithms can hardly be tested on real-life benchmarks directly because we do not know exactly how well the algorithms will perform if the community intensity of the original network changes. erefore, in most previous studies, evaluating the robustness of a community detection algorithm can only be carried out on artificial synthetic benchmarks (e.g., GN and LFR) [8][9][10][11][12][13][28][29][30][31], whose structural characteristics differ significantly from real-life networks [14,15,[23][24][25][26][27].…”
Section: Benchmarks With Varying Community Intensitymentioning
confidence: 99%
“…As the number of each real-life network is only one and the community intensity within the network cannot be adjusted, it is impossible to know how the detection accuracy of the algorithm changes when the network community structure gradually blurs. erefore, in the existing research studies, the robustness evaluation of algorithms still needs to rely on synthetic benchmarks, such as GN and LFR, which can be constructed as a series of networks with gradually varied community intensity [12,13,[28][29][30][31]. However, the modification of mesoscale structures (i.e., community) in existing synthetic benchmarks, often changes with microscale characteristics, which affects the accuracy of robustness assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, we have shown that by incorporating local search operators into generic metaheuristic optimization algorithms, we can significantly improve the speed and accuracy for community detection in large scale biological networks [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Another problem of using generic metaheuristic optimization algorithms is that the search operators, i.e., perturbation [ 5 ], mutation and crossover [ 14 ], are not specifically designed for active module identification, which might result in mediocre search performance in terms of speed and accuracy. In our previous works, we have shown that by incorporating local search operators into generic metaheuristic optimization algorithms, we can significantly improve the speed and accuracy for community detection in large scale biological networks [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%